PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS IV SD NEGERI 114615 TANJUNG MANGEDAR - Siti Humairoh; Sujarwo; Ahmad Laut Hasibuan; Sutikno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Project Based Learning (PjBL) model on students’ learning outcomes in the Natural and Social Sciences (IPAS) subject on the topic of human body parts for fourth-grade students at SD Negeri 114615 Tanjung Mangedar. This research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The research subjects consisted of two classes: Class IV A as the experimental group with 24 students and Class IV B as the control group with 22 students. Data were collected through pretest and posttest in the form of essay questions. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing with an independent samples t-test. The results showed that the average posttest score of the experimental class taught using the PjBL model was 84.17, which was higher than that of the control class taught using conventional learning, with an average score of 64.54. The results of the t-test indicated that the calculated t value was greater than the t table value, indicating that the alternative hypothesis was accepted. Therefore, it can be concluded that the Project Based Learning (PjBL) model has a significant effect on improving students’ learning outcomes in the IPAS subject for fourth-grade students at SD Negeri 114615 Tanjung Mangedar.